1999
DOI: 10.1046/j.1365-2540.1999.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Mesoamerican populations of mahogany (Swietenia macrophylla), assessed using RAPDs

Abstract: Swietenia macrophylla King, a timber species native to tropical America, is threatened by selective logging and deforestation. To quantify genetic diversity within the species and monitor the impact of selective logging, populations were sampled across Mesoamerica, from Mexico to Panama, and analysed for RAPD DNA variation. Ten decamer primers generated 102 polymorphic RAPD bands and pairwise distances were calculated between populations according to Nei, then used to construct a radial neighbour-joining dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 25 publications
7
59
1
7
Order By: Relevance
“…The estimate of ⌽ ST derived here for P. chiapensis (0.226) is substantially higher than values derived for other tree species using similar methods (Isabel et al, 1995;Allnutt et al, 1999Allnutt et al, , 2001Gillies et al, 1999;Bekessy et al, 2002). This value is also high compared to values for other pine species using a variety of different markers.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The estimate of ⌽ ST derived here for P. chiapensis (0.226) is substantially higher than values derived for other tree species using similar methods (Isabel et al, 1995;Allnutt et al, 1999Allnutt et al, , 2001Gillies et al, 1999;Bekessy et al, 2002). This value is also high compared to values for other pine species using a variety of different markers.…”
Section: Discussioncontrasting
confidence: 66%
“…The AMOVA programme generates ⌽ statistics (Excoffier et al, 1992), which are analogous to Wright's F ST (Wright, 1951). This approach has been widely adopted in the analysis of RAPD data (eg, Gillies et al, 1997Gillies et al, , 1999Allnutt et al, 1999;Nybom and Bartish, 2000;Ehtisham-ul-Haq et al, 2001;Bekessy et al, 2002), allowing comparison of results with a variety of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bands were numbered in order of increasing primer number and fragment size (Table 2). (Gillies et al, 1999), 0.45 for Cedrela odorata (Gillies et al, 1997), and 0.59 for Poulsenia armata (Aide and Rivera, 1998). Care should be taken when comparing values across studies because they are influenced by the genetic markers employed and because of inconsistent methods of calculating diversity (eg, Gillies et al, 1999;Martin and Bermejo, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in Costa Rica found that more than 96% of the genetic variation in Dendropanax arboreus, Inga thibaudiana, and Protium glabrum was attributable to differences within plots along a 9 km transect (Schierenbeck et al, 1997). However, population differentiation does tend to rise with increasing distances between populations and may be exacerbated by forest fragmentation (Hall et al, 1996;Aide and Rivera, 1998;Gillies et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…While evidence is lacking for decreased genetic variation among human-impacted populations of Swietenia spp. (Gillies et al 1999;White et al 1999), the record of logging in Mexico may be sufficiently long relative to the mahogany life cycle to register discernible population genetic change in harvested forests.…”
Section: Levels Of Genetic Variation Within Mesoamerican Populationsmentioning
confidence: 99%